Pictorial versus written asthma action plans for youth: initial impact on regimen knowledge, medication adherence, symptom control, and family satisfaction. (2nd September 2022) - Hynes, Lisa; Durkin, Kristine; Ewell, Thomas; Lilly, Christa; Williford, Desireé N.; Ahrabi-Nejad, Corrine; Noel, Destiny; Kothari, Viral; Skoner, David; Duncan, Christina L.
Abstract: Objective: Asthma action plans (AAP) are recommended to guide asthma management. Written AAPs (WAAPs) are under-utilized and can be difficult to understand. Our study designed and tested a simplified pictorial AAP (PAAP). We hypothesized that better outcomes would be obtained for youth with the PAAP. Methods: One hundred and sixty-nine (169) youth (aged 8–17; AAP-naïve) were screened for this pilot, 2-arm randomized controlled trial. Feasibility, usability and preliminary efficacy of PAAP compared to a WAAP, for improving outcomes (inhaled corticosteroid (ICS) adherence, symptom control, AAP knowledge, AAP satisfaction) were assessed quantitatively. Youth received an AAP from their physician after completing baseline measures and completed measures at three additional time points (1-, 3-, and 6-month). Results: Forty-five youth were recruited (PAAP = 22; WAAP = 23). Youth AAP knowledge was higher for the PAAP group compared to the WAAP group ( p  = .017). ICS adherence did not differ between groups, over time, or based on prescribed dosing; however, for WAAP participants, adherence was lower with a higher daily prescription (4 puffs) relative to a lower dose ( p  = .006). Symptom control improved with both AAPs, but the change was not statistically significant. Lung function did not change significantly by AAP type or time, and literacy variables were not related significantly to outcomes. Youth satisfaction with AAP improved significantly for the PAAP group compared to the WAAP group ( p  = .03). Conclusions: Higher AAP knowledge and satisfaction among youth in the PAAP group suggests that structured education from a physician using a PAAP is beneficial. Intervention and study design insights gained will guide future research.